2021
DOI: 10.1186/s40561-021-00166-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of virtual reality meditation on college students’ exam performance

Abstract: Advocates of meditation claim that it can improve various aspects of life, including health, attention, thinking, and learning. The purpose of this empirical, quantitative, between-subject study was twofold. First, it compared the effectiveness of meditation delivered through virtual reality versus video, as measured by students’ test scores. Second, the study provided insights on the use of meditation, whether via virtual reality or video, as a way to positively affect well-being. T-test analysis showed virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Decreased anxiety seems to be the main psychological outcome of mindfulness-based interventions mediated by VR. This specific emotional improvement was reported by Crescentini et al [ 47 ]; Tarrant et al [ 46 ]; Kaplan-Rakowski et al [ 43 ], using both nature-based VR scenarios as well as MOM training in train stations. The effect could extend to other negative mood states such as Anger, Depression, and Tension, as suggested by Tarrant et al [ 41 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Decreased anxiety seems to be the main psychological outcome of mindfulness-based interventions mediated by VR. This specific emotional improvement was reported by Crescentini et al [ 47 ]; Tarrant et al [ 46 ]; Kaplan-Rakowski et al [ 43 ], using both nature-based VR scenarios as well as MOM training in train stations. The effect could extend to other negative mood states such as Anger, Depression, and Tension, as suggested by Tarrant et al [ 41 ].…”
Section: Discussionsupporting
confidence: 75%
“…The previous system, Oculus Rift DK2, which updated the DK1, guarantees high performance with a resolution of 960x1080 per eye, a refresh rate of 75 Hz, and 100° of FOV. In contrast, the Oculus Go VR headset [ 41 , 43 ] is a standalone immersive VR system. It has a fluid display (60–72 Hz) with minor FOV to 101°, and a resolution of 1280x1440.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Rakowski et al [131] investigated whether an immersive meditation intervention could be more beneficial than a video-based meditation in a sample of 61 students. VR-based meditation was found to be more or just as effective as video-based intervention.…”
Section: Decenteringmentioning
confidence: 99%
“…Workers at risk of burnout were found to significantly increase the above skills, indicating the importance of implementing such methods in places for increasing workers' well-being and productivity [110,132]. In addition, typically developing students as well as students with special educational needs significantly increased a wide range of self-regulation skills [108,122,131]. Students were more able to concentrate, effectively manage exam anxiety, be self-confident, and achieve a state of emotional balance [108,131].…”
Section: Xr Mindfulness Training: Opportunities Challenges and Future...mentioning
confidence: 99%
“…Studies on the use of VR in meditation have shown a slight increase in positive effects and a state of mindfulness in users after the meditation experience [ 49 ]. One study showed that VR meditation was more successful in reducing pre-exam anxiety in college students than watching a meditation video, where 71% of those using VR reported lower anxiety levels compared to 47% of the control group [ 50 ]. VR mediation has been shown to be useful in calming healthcare workers, especially during the COVID-19 pandemic.…”
Section: Reviews Of Vr Technology Applicationsmentioning
confidence: 99%